Program PHBS di Masjid Tuntungan dalam Mewujudkan Jamaah yang Produktif dalam Peduli Sehat - Vaudi, Tazkia; Nabilla, Maisya; Afghani, Zaid Al; Riski, Mutiara; Praramadhani, Nikita; Mardiyah, Atika; Hasibuan, Dinda Syahfitri; Darma, Eka Putri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Clean and Healthy Living Behavior (CHLB) is a step that must be taken to achieve optimal health for every human being. The implementation of CHLB in the mosque environment can mobilize and empower the caretakers and congregation to live clean and healthy. The purpose of this study is to realize the CHLB program in the Tuntungan mosque so that the congregation can be productive in caring for health. The research method used is qualitative with data collection techniques including interviews, observation, and documentation. Based on the research results, cleanliness in the Tuntungan mosque environment is already quite good, but there are still people who pay less attention to cleanliness, and the condition of the water in the mosque still feels rusty. The conclusion of this study is that there are still many mosque congregations who have not implemented CHLB in the Tuntungan mosque.